Transformasi Kepemimpinan Pendidikan Era Disrupsi - Rita Dwi Nawanti; Wahyudi Taufan Santoso; Bambang Sumardjoko; Achmad Fathoni (South Sulawesi Education Development (SSED), 2024)
The purpose of this study is to determine the role of educational leadership in times of significant change and upheaval. The methodology used in this research utilizes a library-based research method or strategy. Library research is a systematic approach to collecting, examining, and interpreting materials from various library sources or related literature. The purpose of this research is to gain a comprehensive understanding of the topic or research problem under investigation. The findings of this study show that conversations around the period of disruption and leadership are associated with two very contrasting phenomena. Disruption refers to the global challenges that result in change over time due to technology, while leadership refers to the set of skills that a leader must possess to advance the environment in order for an organization (from a small group to a country) to survive and not sink but now advance through the use of technology. At the very least, you will know the psychological requirements one needs to be a leader when you lead one. It is not enough for a person to have psychological qualities or traits that enhance their leadership capacity for them to be deemed fit or appropriate for the role, they must also better demonstrate leader-like behavior within their team or among their members.